2022
DOI: 10.1097/gox.0000000000004206
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Location of Pulp Glomus Tumor: A Case Study and Literature Review

Abstract: Summary: Glomus tumors are painful, benign tumors that develop from the glomus bodies. They account for less than 1% of tumors in hand, and less than 10% present in the pulp of the digits. Cold hypersensitivity, increased pinprick sensitivity, and paroxysmal pain are common glomus tumor symptoms. We describe a 27-year-old man who came with pain in the right little digit, confined to the pulp for 10 years. The tip of the finger was extremely sensitive to touch, and the pain worsened in a cold atmosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the index case, the clinical symptom was present for four years. Studies have reported a mean duration ranging from 1.9 years to 10 years [10]. These tumors can be categorized as solitary or multiple, with the solitary type being more frequent and typically affecting middle-aged females, often localized to the distal phalanges of the fingers [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the index case, the clinical symptom was present for four years. Studies have reported a mean duration ranging from 1.9 years to 10 years [10]. These tumors can be categorized as solitary or multiple, with the solitary type being more frequent and typically affecting middle-aged females, often localized to the distal phalanges of the fingers [9].…”
Section: Discussionmentioning
confidence: 99%